2011
DOI: 10.1111/j.1600-0501.2011.02289.x
|View full text |Cite
|
Sign up to set email alerts
|

Is oral health‐related quality of life stable following rehabilitation with mandibular two‐implant overdentures?

Abstract: The effect of mandibular two-IODs on OHRQoL is stable over a 2-year period. The large magnitude of effect of this treatment supports its clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…The treatment with new CD in the maxilla only or in both jaws significantly reduced the OHIP-EDENT scores over the complete study period of 24 months, with the lowest values at the last follow-up visit. 26 Another study observed no change in the OHIP-20 scores between 12 and 24 months after treatment with CD, 28 indicating a stable level of OHRQoL impairment. In the present study, the OHIP scores slightly increased in the CD group from the 12-month follow-up to the 24-month followup, a fact that appears to be in contrast to the findings mentioned above.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The treatment with new CD in the maxilla only or in both jaws significantly reduced the OHIP-EDENT scores over the complete study period of 24 months, with the lowest values at the last follow-up visit. 26 Another study observed no change in the OHIP-20 scores between 12 and 24 months after treatment with CD, 28 indicating a stable level of OHRQoL impairment. In the present study, the OHIP scores slightly increased in the CD group from the 12-month follow-up to the 24-month followup, a fact that appears to be in contrast to the findings mentioned above.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 For prosthodontics, however, most of the studies reported only short-term effects of improved OHRQoL directly after or a few weeks subsequent to treatment. [22][23][24] Studies with longer follow-up periods are rare and mainly limited to specific treatment options such as a 12-month study on double crownretained removable partial dentures, 25 three 24-month studies on conventional and implant-supported complete dentures, [26][27][28] and a 5-year study on different treatment option for patients with shortened dental arches. 29 Only one study identified reported OHRQoL after the full range of conventional, i.e., without implants, prosthodontic treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the retrieved studies showed that patients with hypodontia are less disabled than expected, as demonstrated by the moderate OHIP and CPQ scores. For example, according to a study in edentulous wearers of full dentures before implant stabilization, the baseline OHIP score was much higher (54.2) [36], compared to a mean baseline score in the studies included here of 27.8. This observation may be explained by the adaptation of the juvenile hypodontia patients to the situation from early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…13 These improvements were found to be stable over time. 14 Randomized, within-subject, crossover trials on mandibular two-implant-supported prostheses indicated similar patient satisfaction with either a mandibular long-bar implant overdenture or even a fixed fulldental prosthesis. 15,16 Therefore, a two-implant supported overdenture is considered 'the standard of care' for edentulous lower jaws 5,17 , except for individuals who consider a removable denture as a foreign body.…”
Section: Introductionmentioning
confidence: 99%